2011
DOI: 10.1007/s11368-011-0428-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the potential effect of different land cover management practices on sediment yield from an abandoned farmland catchment in the Spanish Pyrenees

Abstract: Purpose Sediment delivery from headwater catchments to reservoirs is a serious threat to reservoir sustainability and is a critical issue in Mediterranean environments where water resources are scarce. In this study we assessed the consequences of two landscape management scenarios (natural vegetation recovery and scrub clearance) on soil erosion and sediment yield. The results were analyzed in relation to predicted and measured rates of soil erosion and sediment yield, with the aim of promoting better managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 58 publications
1
24
1
3
Order By: Relevance
“…Nevertheless, experiences in other Spanish regions suggested that the clearing of shrubs in abandoned fields increases livestock potential, improves the quality of the landscape and reduces the risk of fire because of the creation of a mosaic of vegetation and topography that breaks the homogeneity that is a feature of the slopes of abandoned fields (Lasanta et al ., , , ). On the other hand, the application of predictive models in a small experimental catchment characterized by abandoned land in the Spanish Pyrenees (Arnás catchment), covered by shrubs and small forest areas, showed that clearing shrubs for conversion into grazing meadows would simply increase the erosion rates (López‐Vicente et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, experiences in other Spanish regions suggested that the clearing of shrubs in abandoned fields increases livestock potential, improves the quality of the landscape and reduces the risk of fire because of the creation of a mosaic of vegetation and topography that breaks the homogeneity that is a feature of the slopes of abandoned fields (Lasanta et al ., , , ). On the other hand, the application of predictive models in a small experimental catchment characterized by abandoned land in the Spanish Pyrenees (Arnás catchment), covered by shrubs and small forest areas, showed that clearing shrubs for conversion into grazing meadows would simply increase the erosion rates (López‐Vicente et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…4) was not unexpected due to changes in land uses that occurred in the past century. This reflects likely succession states between former agricultural areas that are partly reverting to natural forests after land abandonment (e.g., López-Vicente et al, 2011) which could contribute to overlapping source data. Also the influence of similar lithological characteristics of the three overlapping points from forest source with those from the agricultural source may also account for the lack of discrimination between these two sources.…”
Section: Discussionmentioning
confidence: 99%
“…En este contexto cabe señalar los efectos de los cambios de los usos del suelo en la cuenca sobre la producción de sedimentos y generación de escorrentía, tal y como indican numerosos trabajos en España en diferentes contextos hidroclimáticos (por ej. Beguería et al, 2006;García-Ruíz, 2010;López-Vicente et al, 2011;Sanchis-Ibor y Segura-Beltrán, 2014). De especial interés además es el estudio de los efectos de la regulación de los caudales por embalses, sobre todo en un contexto climático mediterráneo, donde las presas son un elemento clave en la gestión de los recursos hídricos superficiales.…”
Section: Introductionunclassified